UNLOCKING THE POWER OF PRECISION MEDICINE PERSONALIZED TREATMENTS FOR A HEALTHIER FUTURE - Dr. Suresh Kanna Subramaniam; Dr. Umashankar. R.; Dr. Karthikeya. T. M.; Dr. Vinatha. M. C. (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The convergence of artificial intelligence (AI) and precision medicine represents a groundbreaking shift in healthcare. By harnessing the power of AI to analyze extensive patient data, including genomics, medical records, and clinical trial information, we can achieve more accurate diagnoses, tailor treatment plans to individual characteristics, and detect diseases earlier. This not only leads to improved patient outcomes but also accelerates drug discovery and reduces healthcare costs by optimizing treatment strategies. Nevertheless, this transformative potential comes with ethical and regulatory considerations, such as data privacy and algorithm fairness. Collaboration between healthcare professionals, data scientists, and geneticists is crucial for effective implementation, and ongoing research is essential to refine AI algorithms and ensure their seamless integration into clinical practice. As we continue to advance in this field, the convergence of AI and precision medicine holds promise for addressing complex healthcare challenges and providing personalized, effective care at scale.